A new azodioxy-linked porphyrin-based semiconductive covalent organic framework with I2 doping-enhanced photoconductivity. Issue 23 (10th March 2016) - Nath, Bhaskar; Li, Wen-Hua; Huang, Jia-Hong; Wang, Guan-E.; Fu, Zhi-hua; Yao, Ming-Shui; Xu, Gang
Abstract : A homogeneous solution phase reaction was employed to synthesize an azodioxy-linked porphyrin-based semiconductive covalent organic framework (COF), namely POR-COF. The iodine-doped POR-COF shows a significantly enhanced photoconductive behavior. Abstract : A room-temperature solution phase reaction was developed to synthesize a covalent organic framework (COF) for the first time. The synthesized azodioxy-linked porphyrin-based COF (POR-COF) possesses a 2D chess board-like structure in the ab -plane and a 1D channel with an open-window size of around 1.9 nm along the c -axis in the modeled crystal structure. The electrical conductivity of POR-COF increases by more than 3 orders of magnitude through I2 doping. The photoconductivity of the I2 -doped COF material was also studied firstly. POR-COF shows interesting doping-enhanced photo-current generation.